Matrine relieved DHAV-1-induced hepatocyte excessive interferon and pyroptosis by activating mitophagy - Weiran Wang; Xiang Fu; Bolin Gu; Mengxin Hu; Jiaguo Liu (Poultry Science)
Duck hepatitis A virus type 1 (DHAV-1) is a significant pathogen affecting ducklings, capable of causing rapid mortality and adversely impacting the development of the duck industry. Matrine, the primary active ingredient in various Chinese herbal medicines, has demonstrated antiviral and anti-inflammatory properties. Nevertheless, the effects and mechanisms of action of matrine against DHAV-1 infection remain unclear. This research investigates the effects of matrine on DHAV-1 infection and elucidates the mechanisms involved. We found that matrine mitigated the excessive retinoic acid-inducible gene I (RIG-I)-like receptor (RLR) signaling response, pyroptosis, and mitochondrial damage induced by DHAV-1 in duckling livers and duck embryonic hepatocytes (DEHs). Additionally‌, by incorporating the autophagy inhibitor chloroquine, we observed that the effects of matrine on the regulation of excessive interferon (IFN) production, pyroptosis, mitochondrial damage, and oxidative stress were reversed. Overall, matrine inhibited excessive IFN production and pyroptosis by promoting mitophagy, suggesting that matrine may act as a possible therapeutic agent for addressing DHAV-1 infection and other viral hepatitis.